Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Soal-Soal HOTS (Analisis Kuantitatif) - Putri Bintang; Lence Ristiani; Hospa Lestari; Ahmad Walid (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This analysis aims to describe students' critical thinking skills in solving Higher Order Thinking Skill (HOTS) questions. The type of analysis used is quantifiable-qualitative descriptive research. This analyst is carried out for junior high school students. The subjects used in this study were 3 students taken from class VIII, namely 1 student with a moderate category, 1 student with a low category and 1 student with a very low category. Subject taking based on the test results obtained by the student. Arithmetic sequence and series materials are given to see students' critical thinking skills in solving HOTS questions. The results showed that students' critical thinking ability in solving HOTS questions in the arithmetic sequence and series of the four questions given was still very low. Based on the test results and interviews of the three subjects, it shows that students are more likely to find it difficult when entering the stage of analyzing and evaluating. Students often forget the concepts related to the problem, making it difficult for them to solve the problem, especially in the form of a HOTS question which is more contextual and requires a high ability to analyze and evaluate.